Evaluasi program Corporate Social Responsibility sebagai salah satu upaya untuk mendapatkan sertifikasi sustainable palm oil pada PT Argo Indomas - , Suriany, SE, DR. Eko Suwardi M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Businesses today base their strategic management decision in the increase of sales, profit, and social responsibility of companies. In the globalization era, businesses are related to the social responsibility of companies or what is called as Corporate Social Responsibility (CSR). This social responsibility is not only viewed as an added value to improve the social condition in the proximity of companies, but also as a strategy to improve and develop their business on a wider market segment, namely across countries and regions. Currently, palm oil industry is being closely watched by the world because it is not utilizing sustainability concept optimally, not improving the welfare of people living in the proximity of the plantation adequately, and more importantly, is causing damage to the environment. RSPO (Roundtable Sustainable Palm Oil) Certification, which consists of principles and criteria, has a role to bridge producer and consumer countries with regards to the fulfillment of sustainable palm oil plantations and Corporate Social Responsibility towards the environment. The author in this case conducts case study research by using quantitative analysis method through survey data collection. The objective of this research is to provide recommendation on the sustainability of CSR in a company. The author attempts to analyze how CSR that is being implemented by PT. Agro Indomas supports the feasibility of Sustainable Palm Oil Certification / CSPO. The first stage of the research is descriptive analysis of the implementation of CSR program to know the assessment of stakeholders on CSR Program, which is done through CSR dimension category analysis using questionnaire with total respondents of 53 people. The CSR dimensions analyzed refer to Nor Hadi (2011), namely environment, community, staff, energy, product, etc. Next, gap analysis is performed on CSR implementation to obtain information in the form of gap value between program implementation and interest level expected by stakeholders, so that aspects that should be improved in CSR program implementation can be evaluated. This analysis includes 2 stages, the first stage is to know the difference between interest level and satisfaction level experienced by stakeholders, and to establish medium or standard value from both satisfaction and interest side using quadrant descriptive statistics analysis, Important Performance Analysis (IPA), which is an evaluation on the fourth quadrant from the first gap analysis stage, in which it is interpreted that these aspects are importantly valued by stakeholders, but they are not satisfied by the performance of management. Next, SWOT analysis is performed to assess some internal and external aspects of the company, which will theoritically categorized by the author into the strengths and weaknesses of the company. This analysis uses primary data obtained through analysis result of focus group discussion on the expectation of stakeholders, observation of company sistem on the field and secondary data of literature research. The result of these three stages is compiled into data to formulate CSR factors and company SWOT so that the company can establish its priority in improving program management and company management in order to achieve feasibility for RSPO certification. A questionnaire is made based on FGD result and is filled by 53 respondents. The analysis of these dominant factors uses multivariant inferrential statistics analysis, Confirmatory Factor Analysis (CFA). From the series of analysis results, in general CSR program of PT. Argo Indomas has been well performed, which is proven by high categorization score of all CSR dimensions. From six CSR dimensions elaborated in 63 indicators, there are 39 indicators which are considered important by stakeholders. Out of these 39 indicators, there are 21 indicators deemed not to have been implemented optimally due to the activities have not fulfilled the expectation of the stakeholders. From 6 CSR dimensions, 5 of them are significant factors in forming CSR variable. Staff dimension is the most dominant factor in CSR program. Furthermore, from SWOT analysis, there are 10 aspects that are the threats and weaknesses of the company that need to be improved to obtain CSPO. From 3 SWOT dimensions, (environment, economy, and social), which according to stakeholders are the weaknesses and threats of the company, all of them are significant factors in forming SWOT variable, and social dimension is the most dominant factor that needs to be developed and its indicators improved. As one of the efforts to obtain CSPO, the author recommends establishing strategic steps to improve indicators that are importantly valued by stakeholders. Such indicators include waste management and processing, research related to environment, environmental rehabilitation and reclamation, environmental planning and management system, compliance to rules and regulations, help repairing road and neighborhood lighting, managing unemployment in the proximity of the company, improving the welfare and economy of the surrounding people, help in health care, clean water, help in art and culture, help in sports, help in relieving natural disaster, praying and public facilities, partnership and harmony with surrounding people, tolerance among members of the community and religious communities, cooperation with national and international institutions to improve peopleâs quality of life, program to eradicate HIV and drug abuse, health insurance, improving skills, education, and training, help in providing housing and education for the staffâs children and families, implementation of good corporate code of conduct, leave programs and gender bias issues.